Diet and resting state brain functional connectivity across the adult lifespan. (31st December 2021) - Gu, Yian; Burns, Eleanna; Habeck, Christian; Mensing, Ashley; Noofoory, Diala; Babukutty, Reshma S; Stern, Yaakov
Abstract: Background: Healthy diets are associated with reduced risk of Alzheimer's disease, better cognition, and healthier brain structural measures. However, the relationship between nutrition and diet and resting‐state functional connectivity (rsFC) remains unclear. Method: The current study included 370 individuals across the adult lifespan (20–80 years). Dietary information was self‐reported using a food frequency questionnaire, from which the Mediterranean diet score (MeDi, range 0‐55) was calculated. Participants underwent a resting‐state imaging on a 3T MRI scanner. Within‐network and between‐network connectivity values were computed based on 10 predefined networks. Multivariable linear regression models were used to examine the association between tertiles of MeDi and rsFC in the overall study population as well as within three age groups [99 young (20‐45 years); 147 middle‐aged (46‐65 years), and 124 older adults (66‐80 years)]. Similar analyses were done for omega‐3 polyunsaturated fatty acids (PUFA) consumption. All models were controlled for potential confounders including age, sex, education, race/ethnicity, caloric intake, IQ, and scrubbing percentage. Result: Among all subjects, higher MeDi was associated with lower global within‐network connectivity (highest vs. lowest tertile of MeDi, b=‐0.014, p=0.031) but not with global between‐network connectivity. Among all ten individual networks, higher MeDi was associated with lower within‐network connectivity of the default‐mode network (DMN) but not with any other individual networks. Analyses stratified by age groups found the associations between rsFC and diet could mainly be seen in older adults. Among the somatomotor networks, higher MeDi was associated with higher within‐network connectivity for hand and auditory networks but was associated with lower within‐DMN connectivity. For between‐network connectivity, higher MeDi was associated with higher global connectivity (highest vs. lowest tertile of MeDi, b=0.019, p=0.015) as well as higher connectivity for almost all individual networks except for the DMN. No association between MeDi and rsFC was found in younger and middle‐aged adults. Findings on omega‐3 PUFA were similar to MeDi, except that omega‐3 PUFA was not associated with within‐network connectivity of the DMN. Conclusion: Our findings suggest that in older adult, healthier dietary factors are associated with higher both within‐ and between‐ network connectivity except for within‐DMN rsFC values.